1970
DOI: 10.5424/sjar/20110904-235-11
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Real-time ultrasonography for early pregnancy diagnosis and incidence of embryonic/foetal mortality in farmed Iberian red deer hinds

Abstract: The main objective of the present study was to evaluate the accuracy of the trans-rectal ultrasonography technique applied to the Iberian red deer hinds since it has not been previously documented in Spain. Experimentation was also used to test the hypothesis that a lower fertility in young hinds could be due to an increment in embryonic or foetal mortality. For this purpose, 116 hinds divided in three groups depending on its age (young, adults and senescent) were examined by rectal ultrasonography and the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In free-ranging caribou ( Rangifer tarandus ), Russell et al ( 1998 ) reported embryonic mortality in 8.5 % (12/141) of the investigated radio-collared females, using repeated hormone analyses (progesterone, pregnancy-specific protein). Using transrectal ultrasonography after mating, and studying subsequent parturition rates, Gómez-Nieto et al ( 2011 ) stated that 13.0 % (6/46) of captive red deer ( Cervus elaphus ) most likely had experienced embryonic mortality. Embryonic mortality and lack of fertilization of oocytes are well-known occurrences in domestic species, e.g., cattle (Diskin et al 2011 ; Hanly 1961 ; King 1991 ), sheep (Cognie et al 1975 ; Dutt and Simpson 1957 ; Vázquez et al 2009 ; Viñoles et al 2012 ), goats (Armstrong and Evans 1983 ; Gonz et al 2004 ; Shelton 1978 ), pigs (Dziuk 1968 ; Geisert et al 2007 ; Soede et al 1994 ), and horses (Ball et al 1986 ; Dippert et al 1994 ; Newcombe and Cuervo-Arango 2011 ), and underlying causes of may be infectious (bacteria, virus, parasites, fungi) or of genetic, endocrine, and environmental origin (Diskin et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In free-ranging caribou ( Rangifer tarandus ), Russell et al ( 1998 ) reported embryonic mortality in 8.5 % (12/141) of the investigated radio-collared females, using repeated hormone analyses (progesterone, pregnancy-specific protein). Using transrectal ultrasonography after mating, and studying subsequent parturition rates, Gómez-Nieto et al ( 2011 ) stated that 13.0 % (6/46) of captive red deer ( Cervus elaphus ) most likely had experienced embryonic mortality. Embryonic mortality and lack of fertilization of oocytes are well-known occurrences in domestic species, e.g., cattle (Diskin et al 2011 ; Hanly 1961 ; King 1991 ), sheep (Cognie et al 1975 ; Dutt and Simpson 1957 ; Vázquez et al 2009 ; Viñoles et al 2012 ), goats (Armstrong and Evans 1983 ; Gonz et al 2004 ; Shelton 1978 ), pigs (Dziuk 1968 ; Geisert et al 2007 ; Soede et al 1994 ), and horses (Ball et al 1986 ; Dippert et al 1994 ; Newcombe and Cuervo-Arango 2011 ), and underlying causes of may be infectious (bacteria, virus, parasites, fungi) or of genetic, endocrine, and environmental origin (Diskin et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%